Impacts of Air Pollution and Microplastics on Environmental Health in the Era of Climate Change - Rafidha Nur Alifah; Akhmal Raziq Kharazi; Umi Masviroh (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Environmental health challenges in the twenty-first century increasingly arise from the interaction between atmospheric pollution, plastic contamination, and climate change. This study examines the impacts of air pollution and microplastic exposure on environmental health using a quantitative descriptive approach combined with a systematic literature review based on secondary data. Scientific articles were retrieved from PubMed, Scopus, and ScienceDirect, resulting in 156 initial publications, of which 38 studies met the inclusion criteria and were analyzed. The synthesis integrates global datasets from the World Health Organization, Institute for Health Metrics and Evaluation, OECD reports, and national environmental statistics. Findings indicate that ambient air pollution contributes to approximately 6.67 million premature deaths annually, with average PM₂.₅ exposure reaching 29 µg/m³, substantially exceeding the WHO recommended limit of 5 µg/m³. Global plastic production increased dramatically from 2 million tons in 1950 to 460 million tons in 2021, while only 9% of plastic waste is recycled, facilitating the formation of microplastics detected in human blood, lungs, and gastrointestinal samples. Plastic production also generates approximately 1.8 gigatons of CO₂ emissions annually, strengthening the linkage between pollution and climate change. The results highlight synergistic environmental health risks arising from combined exposure to particulate pollution and microplastics, emphasizing the importance of integrated environmental health policies and climate mitigation strategies..